2014
DOI: 10.1111/jace.12805
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Properties of Acceptor‐Doped Lead‐Free Piezoelectric Ceramics

Abstract: We have studied the processing and electromechanical properties of Mn and Fe‐doped 0.88[Bi0.5Na0.5TiO3]–0.08[Bi0.5K0.5TiO3]–0.04[Bi0.5Li0.5TiO3] piezoelectric ceramics prepared by the mixed oxide route. Different amounts of Mn (0.01, 0.014, 0.015, 0.016, 0.017, 0.02, 0.022) or Fe (0.0125, 0.015, 0.0175) were doped to this lead‐free piezoelectric composition. Ceramics were sintered at different temperatures (1075°C–1150°C) to achieve the highest density and mechanical quality factor. Mn or Fe doping resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Table shows the density and electromechanical properties of undoped and Mn‐doped ceramics sintered at 1100°C extracted from our recent publication . Increasing the Mn concentration up to 1.5 mol%, remarkably enhanced the planar Q m .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table shows the density and electromechanical properties of undoped and Mn‐doped ceramics sintered at 1100°C extracted from our recent publication . Increasing the Mn concentration up to 1.5 mol%, remarkably enhanced the planar Q m .…”
Section: Resultsmentioning
confidence: 99%
“…Piezoelectric planar and thickness coupling coefficients ( k p and k t , respectively) were calculated from the resonance and antiresonance frequencies of the impedance traces, based on the IEEE standards, as explained in Ref. The experimental setup and details of high power measurements can be found in Refs. Disk‐shaped transducers with thickness of 1 mm and diameter of about 12 mm were used for low power as well as high power measurements.…”
Section: Methodsmentioning
confidence: 99%
“…leads to increased Q m as well. 29 While some dopants improve the properties of BNT-100xBT, the effects of acceptor-doping in lead-free piezoelectric ceramics and their correlation to aging are not well-understood and systematic studies are missing. Therefore, it appears timely to evaluate the suitability of aging mechanisms known in PZT when applied to the lead-free system BNT-100xBT, and expand understanding on the possible role of the relaxor character of the material.…”
Section: Piezoelectric Ceramics Introductionmentioning
confidence: 99%
“…While this piezoceramic displayed properties associated with 'soft' PZT piezoceramics, it was later reported that altering its manufacturing technique [13] and acceptor doping gave KNN piezoceramics the potential to exhibit piezoelectric properties and a mechanical quality factor, Q m , which are comparable with hard piezoceramics [14]. Additionally, it has also been reported that BNT piezoceramics have also exhibited Q m , coupling coefficients k t and k p , and dissipation factor, tan δ, which are comparable to hard PZT after acceptor doping with manganese [15,16]. However, lead-free piezoceramics developed for power applications have also demonstrated low sensitivity and typically exhibit a d 33 that is significantly lower than normally observed in hard PZT piezoceramics [14,16].…”
Section: Introductionmentioning
confidence: 99%